A real-world economic analysis of biologic therapies for psoriatic arthritis in Italy: results of the CHRONOS observational longitudinal study - Emanuela Zagni; Micol Frassi; Giuseppa Pagano Mariano; Enrico Fusaro; Claudia Lomater; Patrizia Del Medico; Florenzo Iannone; Rosario Foti; Massimiliano Limonta; Antonio Marchesoni; Bernd Raffeiner; Ombretta Viapiana; et al. (BMC, 2022)
Abstract Background Psoriatic arthritis (PsA) is a chronic, immune-mediated, spondyloarthropathy characterised by musculoskeletal signs and symptoms with associated joint pain and tenderness. The average worldwide PsA prevalence is 133/100,000, while in the Italian population is 90-420/100,000. Traditionally, nonsteroidal anti-inflammatory drugs, glucocorticoid, and disease-modifying antirheumatic drugs have been used in the treatment of PsA. However, for those patients who are not adequately controlled with conventional therapies, the new biologics compounds represent a valid option. Biologic therapies have been shown to be more effective but also more expensive than conventional systemic treatments. Based on the CHRONOS study, the economic analyses presented in this paper aim to assess the annualised direct costs and the cost-per-responder of biologics in a real-world context assuming the Italian National Health System perspective. Methods The economic assessments were carried out on the overall cohort of patients, and on the tumour necrosis factor alpha inhibitors (TNFi) and the secukinumab subgroup, the most prescribed biologic therapies within the CHRONOS study. Results The annual economic impact of PsA in the overall group was €12,622, €11,725 in the secukinumab subgroup, and €12,791 in the TNFi subgroup. Biologics absorbed the main expenditure costs in the treatment of PsA accounting for about the 93% of total costs. At 6 months, secukinumab performed better in all the considered outcomes: cost-per-responder according to EULAR DAS28 and ACR50 response criteria were €12,661- €28,975, respectively, while they were €13,356 - €33,368 in the overall cohort and €13,138 - €35,166 in the TNFi subgroup. At 12 months secukinumab remained the subgroup with the lowest cost-per-responder ratio in EULAR DAS28 and ACR50 response criteria, while TNFi subgroup was the lowest one considered the ACR20. Conclusion Despite some potential methodological limitations, our cost-per-response analysis provides physicians and payers additional insights which can complement the traditional risk-benefit profile assessment and drive treatment decisions.